Improvement of Coxarthrosis Due to Realignment of Pelvic Retroversion Following Spinal Corrective Surgery: A Case Report. Issue 4 (23rd October 2022) - Suzuki, Mayu; Takano, Morito; Iida, Tsuyoshi; Tsukimura, Yasunori; Kaneko, Hironori; Hikata, Tomohiro
Abstract : Case: A 70-year-old woman presented with severe trunk deformity, gait disturbance, and bilateral hip pain. Radiography and magnetic resonance imaging revealed severe spinal kyphosis, bilateral osteoarthritis of the hip joints, and lumbar canal stenosis. A 2-stage corrective surgery for the treatment of spinal kyphosis was performed. Subsequently, the spinopelvic alignment changed remarkably. The spinal symptoms and radiographic parameters improved postoperatively, and bilateral hip pain and range of motion also showed improvement. Conclusion: Corrective surgery for the treatment of degenerative spinal kyphosis affected the spinopelvic alignment, and the symptoms of simultaneous coxarthrosis also improved after the corrective surgery.